EFEK HEPATOPROTEKTOR EKSTRAK Andrographis paniculata Nees (SAMBILOTO) TERHADAP AKTIVITAS ALANIN AMINO TRANSFERASE DALAM PLASMA Rattus norvegicus JANTAN GALUR WISTAR YANG DIINDUKSI PARASETAMOL - ., Yudo Prabowo (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background : Andrographis paniculata contain an active substancesandrographolide which was believed to have a protective effect on the liverand stimulate glutation formation (GSH) for increase hepatoprotector effect inthe form decrease alanin amino transferase (ALT) enzim activity. Objective :the research would investigate the hepatoprotector effect and effective dosesof methanolic extract of Andrographis paniculata in male wistar rats comparedkurkuma as positive control with alanin amino transferase activity ashepatoprotector indicator. Method : the research was pretest and posttestexperimental design. Thirty wistar rat was randomly divided into 5experimental group, negative control (CMC 0,5%), positive control (kurkuma),dose I (500 mg/kgWB), dose II (1000 mg/kgWB), and dose III (2000mg/kgWB) that was induced by parasetamol toxic dose for 7 days. Theresulting data is analyzed with One-Way Anova test continued with LSD posPost Hoc. Results : from phytochemical testing result, Andrographispaniculata methanolic extract contain flavonoid, tanin, saponin, and terpenoidsecondary metabolite. Statistical analysis showed significance differencebetween average ALT activity from control group (negative and positive)against dose I, II, and dose III group of methanolic extract of Andrographispaniculata (p<0,05) at measurement ALT activity posttest. Conclusion :Dose I, II, and dose III group of methanolic extract of Andrographis paniculatahas a hepatoprotector effect in the form decrease alanin amino transferase(ALT) enzim activity in male wistar rat induced parasetamol Keyword : Andrographis paniculata, methanolic extract of Andrographispaniculata, paracetamol, ALT activity, hepatoprotector 1) Medical School, Faculty of Medicine, University of TanjungpuraPontianak, West Borneo. Â 2) Pharmacology Departement, Medical School, Faculty of Medicine,University of Tanjungpura Pontianak, West Borneo. 3) Biochemical Departement, Medical School, Faculty of Medicine,University of Tanjungpura Pontianak, West Borneo.